DYNAMIC ABC STORAGE POLICY IN ERRATIC DEMAND ENVIRONMENTS - Benjamin Pierre; Bart Vannieuwenhuyse; Denis Dominanta; Hendrik Van Dessel (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2003)
The paper describes a dynamic variant of the traditional ABC storage policy. The variant is to be used in manual order picking warehouses where SKUs experience a rather unstable demand. Its objective is to reduce the order picking time. It mainly consists in shifting items between the storage areas A, B and C according to the way their daily number of order lines changes. A few case studies based on computer simulations have shown that this variant can yield interesting time savings if its parameters are chosen with care. One of those case studies is presented in this paper. Because of the pioneering nature of this variant, some ideas for further research are also sketched.